2020
DOI: 10.4143/crt.2019.718
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Testing in Gastric Cancer by the Combined Positive Score of the 22C3 PharmDx and SP263 Assay with Clinically Relevant Cut-offs

Abstract: Purpose We provide a comparison between 22C3 pharmDx and SP263 assay, for evaluating programmed death ligand 1 (PD-L1) expression in advanced gastric cancer (GC) patients.Materials and Methods The PD-L1 immunohistochemistry by 22C3 pharmDx and SP263 assays was performed in the center of the tumor (CT) and invasive margin (IM) in 379 GC tissues using tissue microarrays and interpreted as combined positive score (CPS) and tumor proportion score (TPS). Of the total samples, 55 samples were independently reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 28 publications
(51 reference statements)
2
54
1
1
Order By: Relevance
“…Regarding the scoring algorithms based on PD‐L1 immunohistochemistry, the PD‐L1 CPS rather than the tumour proportion score (i.e. the percentage of positive tumour cells alone) is considered to be a robust and reliable method for predicting the response to pembrolizumab in patients with gastric cancer 17,26 . Kulangara et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the scoring algorithms based on PD‐L1 immunohistochemistry, the PD‐L1 CPS rather than the tumour proportion score (i.e. the percentage of positive tumour cells alone) is considered to be a robust and reliable method for predicting the response to pembrolizumab in patients with gastric cancer 17,26 . Kulangara et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have demonstrated that both the 22C3 antibody and the SP263 antibody are highly concordant in PD‐L1 scoring, suggesting that the two assays may be interchangeable 30–32 . In fact, a recent study performed PD‐L1 immunohistochemistry with both the 22C3 antibody and the SP263 antibody in 379 gastric cancer cases, and showed excellent agreement of the PD‐L1 CPS between the two antibodies; with a CPS cut‐off of 1, 219 (57.8%) and 231 (60.9%) cases were positive for PD‐L1 according to the 22C3 antibody and the SP263 antibody, respectively 26 . Therefore, the results would be most likely to be in agreement with the present results if the 22C3 antibody had been used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EBV status was tested using EBV in-situ hybridization as previously described [ 20 ]. A fluorescein-conjugated EBV encoded small RNA (EBER) oligonucleotide probe (INFORM EBVencoded RNA probe, Ventana Medical Systems) was used, and positive cases were defined as diffuse nuclear reactivity for EBER in tumor cells.…”
Section: Methodsmentioning
confidence: 99%
“…Biomarkers that predict potential responders to anti-PD1/PDL1 therapy have been strenuously investigated by analyzing patient-derived specimens using advanced technology, and several biomarkers, including PDL1 expression, microsatellite instability (MSI), and mutation burden (the number of non-synonymous single nucleotide variants) in tumor cells have been identified [ 168 , 169 ]. However, these are not necessarily correlated with clinical outcomes, and more precise and accurate biomarkers are still being explored in clinical settings.…”
Section: Treatments For Cancer Metastasismentioning
confidence: 99%